Quizizz Application and Its Impact on Advanced Mathematics Learning Outcomes of Prospective Elementary School Teachers in Indonesia - Gunarti, Nur Septia Isma; Wibowo, Setiawan Edi; Haryanto; Sintawati , Mukti; Andriyani, Meyyana (International Journal of Elementary Education, 2022)
The existence of the Covid-19 Pandemic has a major influence on all areas of life, especially in the field of education, one of the impacts of covid is that learning which was originally carried out face-to-face has changed to distance learning which has a negative effect on students, one of which is low student advanced mathematics learning outcomes. . This study aims to analyze the effect of using Quizizz application media on students' advanced mathematics learning outcomes. The type of research is Quasi Experiment, with a research design of Pretest Posttest Control Group Design. The population in this study were 32 students. The sampling of the research was carried out by purposive sampling technique. Data collection in the study was carried out using the test and observation method with the research instrument in the form of an objective test. The research data were then analyzed using descriptive test analysis techniques, normality test, homogeneity test, hypothesis testing and ANOVA test. The results showed that the significance value was 0.000 <0.05 or less than 0.05. So it can be concluded that there is an effect of quizizz media application on the ability of student learning outcomes in advanced mathematics courses.